A prospective, randomized, open label, controlled study investigating the efficiency and safety of 3 different methods of rectus sheath block analgesia following midline laparotomy. Issue 7 (February 2018) - Purdy, Martin; Kinnunen, Mari; Kokki, Merja; Anttila, Maarit; Eskelinen, Matti; Hautajärvi, Heidi; Lehtonen, Marko; Kokki, Hannu
Abstract: Background: There is a controversy regarding the efficacy of rectus sheath block (RSB). The aim of the present study was to evaluate analgesic efficacy and safety of three different methods of RSB in postoperative pain management after midline laparotomy. Methods: A prospective, randomized, controlled, open-label clinical trial with 4 parallel groups was conducted in a tertiary care hospital in Finland. A total of 57 patients undergoing midline laparotomy were randomized to the control group (n = 12) or to 1 of the 3 active RSB analgesia groups: single-dose (n = 16), repeated-doses (n = 12), or continuous infusion (n = 17). Opioid consumption with iv-patient-controlled analgesia pump was recorded, and pain scores and patients' satisfaction were surveyed on an 11-point numeric rating scale for the first 48 postoperative h. Plasma concentrations of oxycodone and levobupivacaine were analyzed. All adverse events during the hospital stay were recorded. Results: Oxycodone consumption was less during the first 12 h in the repeated-doses and in the continuous infusion groups ( P  = .07) and in numerical values up to 48 h in the repeated-doses group. Plasma oxycodone concentrations were similar in all 4 groups. Pain scores were lower in the repeated-doses group when coughing during the first 4 h ( P  = .048 vs. control group), and at rest on the first postoperative morning ( P  = .034 vs. the other 3 groups) and at 24 h ( P  = .006 vs. the single-dose group). All plasma concentrations of levobupivacaine were safe. The patients' satisfaction was better in the repeated-doses group compared with the control group ( P  = .025). No serious or unexpected adverse events were reported. Conclusions: RSB analgesia with repeated-doses seems to have opioid sparing efficacy, and it may enhance pain relief and patients' satisfaction after midline laparotomy.